EDUKASI STUNTING DAN MODERASI BERAGAMA UNTUK MENINGKATKAN KUALITAS PENDIDIKAN ANAK USIA DINI DI DESA PURBA DOLOK - Agustina, Winarti; Situngkir, Ledyana Dwi Mei; Samosir, Rotua; Maranata, Graces; Aritonang, Oktober Tua (Gapenas Publisher, 2025)
Purba Dolok Village, located in Dolok Sanggul District, Humbang Hasundutan Regency, North Sumatra, faces issues of stunting and the need for religious moderation. The majority of the village's population are Christians (92%), with the remainder being Muslims (8%). Stunting, or chronic malnutrition in children, hinders their physical and cognitive development. The main causes of stunting include a lack of knowledge about nutrition, limited access to nutritious food, and inadequate healthcare services. Religious moderation is essential to maintain social harmony amidst religious diversity. A community service program by the Early Childhood Christian Education (PAUD) Study Program aims to address these issues through activities focused on stunting education and religious moderation. These activities include nutrition education for pregnant women and children, interfaith dialogues, and character education based on tolerance in schools. The program results showed an increase in knowledge about nutrition, interfaith harmony, and tolerance among students. Surveys indicated positive responses from participants who committed to applying their new knowledge. This program has provided sustainable positive impacts for the community of Purba Dolok Village and is expected to serve as a model for similar community service initiatives in other regions